Identifying subgroups of teacher burnout in elementary and secondary schools: the effects of teacher experience, age and gender - Alghamdi, Mohammed H.; Sideridis, Georgios (Frontiers in Psychology, 2025)
IntroductionTeacher burnout is a serious problem that requires quick attention and management since it not only compromises educational quality but also strains schools’ financial resources.Research objectiveThe purpose of the present study was to profile burnout indicators for teachers in the Kingdom of Saudi Arabia. A secondary goal was to evaluate the consistency of burnout profiles between elementary and secondary school teachers.MethodParticipants were 703 teachers who participated in the Trends in International Mathematics and Science Study (TIMSS 2019) and were part of the measurement in Saudi Arabia and participated in this study. A series of nested latent class models were run using 1–6 classes to identify an optimal number of interpretable subgroups (latent classes) that best describe the latent construct of teacher burnout in the elementary and high school setting.ResultsThe most important finding was that more than one-third of the teachers reported high levels of burnout irrespective of education level or gender. Furthermore, teachers’ experience and age were positive predictors of burnout with older teachers having significantly elevated levels of burnout. Gender on the other hand did not play a significant moderating role in teachers’ levels of burnout.ImplicationsReducing the number of students in each class, reorganizing the administrative work that has to be done, adding more support personnel to classrooms, and increasing time management skills and tactics via professional development programs are all potential solutions that might help alleviate the problem of teacher burnout.